Emotion and Time Perception: Effects of Film-Induced Mood - Droit-Volet, Sylvie; Fayolle, Sophie L.; Gil, Sandrine (Frontiers in Integrative Neuroscience, 2011)
Previous research into emotion and time perception has been designed to study the time perception of emotional events themselves (e.g., facial expression). Our aim was to investigate the effect of emotions per se on the subsequent time judgment of a neutral, non-affective event. In the present study, the participants were presented with films inducing a specific mood and were subsequently given a temporal bisection task. More precisely, the participants were given two temporal bisection tasks, one before and the other after viewing the emotional film. Three emotional films were tested: one eliciting fear, another sadness and a neutral control film. In addition, the direct mood experience was assessed using the Brief Mood Introspective Scale (BMIS) that was administered to the participants at the beginning and the end of the session. The results showed that the perception of time did not change after viewing either the neutral control films or the sad films although the participants reported being sadder and less aroused after than before watching the sad film clips. In contrast, the stimulus durations were judged longer after than before viewing the frightening films that were judged to increase the emotion of fear and arousal level. In combination with findings from previous studies, our data suggest that the selective lengthening effect after watching frightening films was mediated by an effect of arousal on the speed of the internal clock system.